Development of the Pipette-Tip Micro-Solid-Phase Extraction for Extraction of Rutin From Moringa oleifera Lam. Using Activated Hollow Carbon Nanospheres as Sorbents - Dakalo Lorraine Ndou; Bonakele Patricia Mtolo; Adivhaho Khwathisi; Ashwell Rungano Ndhlala; Nikita Tawanda Tavengwa; Ntakadzeni Edwin Madala (International Journal of Analytical Chemistry)
Herein, a micro-solid-phase extraction (μSPE) method was developed using a pipette tip for rutin extraction, employing activated hollow carbon nanospheres (HCNSs) as the sorbent. Characterization of the activated carbon nanospheres through TGA, FTIR, and SEM analysis confirmed the success of the activation process. The study demonstrated the efficacy of PT-μSPE in rutin extraction under pH 2 conditions with a standard concentration of 2 mg·L−1. The optimal mass of HCNSs was found to be 2 mg, and a loading volume of 500 μL resulted in the maximum recovery of rutin. Propan-2-ol was the best elution solvent with 15 aspirating/dispensing cycles. The correlation of determination (R2) for the calibration curve was found to be 0.9991, and the LOD and LOQ values were 0.604 and 1.830 mg·L−1, respectively. The applicability of the method was demonstrated by extracting rutin from a complex Moringa oleifera leaf extract with the relative standard deviation (RSD) of 3.26%, thereby validating this method as feasible for the extraction of useful bioactive compounds from complex plant samples.